2019
DOI: 10.1038/s41377-019-0177-3
|View full text |Cite|
|
Sign up to set email alerts
|

Reconfigurable beam system for non-line-of-sight free-space optical communication

Abstract: In this paper, we propose a reconfigurable beam-shaping system to permit energy-efficient non-line-of-sight (NLOS) free-space optical communication. Light is steered around obstacles blocking the direct communication pathway and reaches a receiver after reflecting off of a diffuse surface. A coherent array optical transmitter (CAO-Tx) is used to spatially shape the wavefront of the light incident on a diffuse surface. Wavefront shaping is used to enhance the amount of diffusely reflected light reaching the opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(46 citation statements)
references
References 33 publications
0
42
0
Order By: Relevance
“…There are two interesting points to explore in our follow-up research plan. 1) The intelligent reflective surface technology in reference [41] can transform LOS link into NLOS link, which may be combined with the research in this paper to produce new application. 2) As an effective signal to exploit the adjacent sub-channels instead of interference, this rotation angle MIMO architecture may be used to improve the mobility of devices.…”
Section: Discussionmentioning
confidence: 99%
“…There are two interesting points to explore in our follow-up research plan. 1) The intelligent reflective surface technology in reference [41] can transform LOS link into NLOS link, which may be combined with the research in this paper to produce new application. 2) As an effective signal to exploit the adjacent sub-channels instead of interference, this rotation angle MIMO architecture may be used to improve the mobility of devices.…”
Section: Discussionmentioning
confidence: 99%
“…. (22) The second crucial step of this derivation is to find the location of I R,P , which can be done by exploiting the generalized Snell's law, (13) and (14), to identify the corresponding incident ray to the reflected ray RP via θ i R and φ i R as 4…”
Section: B Irradiance Derivationmentioning
confidence: 99%
“…Moreover, in [12], Valagiannopoulos et al added programmable directivity to the transmitter by covering it with a metasurface. In addition, in [13], Cao et al proposed a beam-shaping system at the transmitter to enable non-line of sight VLC using coherent optical transmitter array. In [14], Deng et al proposed and demonstrated a reconfigurable mirco-mirrors based beam-steering system for FSO inter-rack networks of data centers.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, OWC can largely solve the shortage of radio spectrum resources. [3] Visible light communication (VLC) [4] and beamsteered infrared (IR) light communication (BS-ILC) [5,6] are the two main technical directions of OWC. VLC transports data over LED illumination systems and multiple users share the VLC capacity.…”
Section: Introductionmentioning
confidence: 99%